Recipient Comorbidity and Survival Outcomes After Kidney Transplantation: A UK-wide Prospective Cohort Study. Issue 6 (June 2020) - Wu, Diana A.; Robb, Matthew L.; Forsythe, John L.R.; Bradley, Clare; Cairns, John; Draper, Heather; Dudley, Christopher; Johnson, Rachel J.; Metcalfe, Wendy; Ravanan, Rommel; Roderick, Paul; Tomson, Charles R.V.; et al.
Abstract : Background: Comorbidity is increasingly common in kidney transplant recipients, yet the implications for transplant outcomes are not fully understood. We analyzed the relationship between recipient comorbidity and survival outcomes in a UK-wide prospective cohort study—Access to Transplantation and Transplant Outcome Measures (ATTOM). Methods: A total of 2100 adult kidney transplant recipients were recruited from all 23 UK transplant centers between 2011 and 2013. Data on 15 comorbidities were collected at the time of transplantation. Multivariable Cox regression models were used to analyze the relationship between comorbidity and 2-year graft survival, patient survival, and transplant survival (earliest of graft failure or patient death) for deceased-donor kidney transplant (DDKT) recipients (n = 1288) and living-donor kidney transplant (LDKT) recipients (n = 812). Results: For DDKT recipients, peripheral vascular disease (hazard ratio [HR] 3.04, 95% confidence interval [CI]: 1.37-6.74; P = 0.006) and obesity (HR 2.27, 95% CI: 1.27-4.06; P = 0.006) were independent risk factors for graft loss, while heart failure (HR 3.77, 95% CI: 1.79-7.95; P = 0.0005), cerebrovascular disease (HR 3.45, 95% CI: 1.72-6.92; P = 0.0005), and chronic liver disease (HR 4.36, 95% CI: 1.29-14.71; P = 0.018) were associated with an increased risk of mortality. For LDKT recipients, heart failure (HR 3.83, 95% CI: 1.15-12.81; P = 0.029) and diabetes (HR 2.23, 95% CI: 1.03-4.81; P = 0.042) were associated with poorer transplant survival. Conclusions: The key comorbidities that predict poorer 2-year survival outcomes after kidney transplantation have been identified in this large prospective cohort study. The findings will facilitate assessment of individual patient risks and evidence-based decision making. Abstract : Supplemental Digital Content is available in the text.